2021
DOI: 10.3390/vaccines9040399
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Scenarios: A Cost-Effectiveness Analysis for Turkey

Abstract: As of March 2021, COVID-19 has claimed the lives of more than 2.7 million people worldwide. Vaccination has started in most countries around the world. In this study, we estimated the cost-effectiveness of strategies for COVID-19 vaccination for Turkey compared to a baseline in the absence of vaccination and imposed measures by using an enhanced SIRD (Susceptible, Infectious, Recovered, Death) model and various scenarios for the first year after vaccination. The results showed that vaccination is cost-effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
98
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(103 citation statements)
references
References 37 publications
2
98
0
Order By: Relevance
“…These findings mirror cost-effectiveness studies of COVID-19 vaccination done in Turkey and Pakistan that found that although COVID-19 vaccination strategies were cost-effective from a health system's perspective, they were cost-saving from a societal perspective. [39,41] This is in line with arguments from studies that estimate the public health value and impact of vaccination, which argue the need to broaden the perspectives for costeffectiveness analysis of vaccines, as their impact is far-reaching, especially in the context of a pandemic. [42][43][44] These findings have implications for COVID-19 vaccination policy in Kenya and other low-and middleincome countries (LMIC) settings with comparable demographic and COVID-19 epidemiological profiles.…”
Section: Discussionsupporting
confidence: 65%
“…These findings mirror cost-effectiveness studies of COVID-19 vaccination done in Turkey and Pakistan that found that although COVID-19 vaccination strategies were cost-effective from a health system's perspective, they were cost-saving from a societal perspective. [39,41] This is in line with arguments from studies that estimate the public health value and impact of vaccination, which argue the need to broaden the perspectives for costeffectiveness analysis of vaccines, as their impact is far-reaching, especially in the context of a pandemic. [42][43][44] These findings have implications for COVID-19 vaccination policy in Kenya and other low-and middleincome countries (LMIC) settings with comparable demographic and COVID-19 epidemiological profiles.…”
Section: Discussionsupporting
confidence: 65%
“…The result of cost-effectiveness analysis in Turkey demonstrates that any vaccine with an effectiveness of more than 80% and coverage of more than 30% would be cost saving. With coverage of about 50%, the vaccine's effectiveness should be at least around 55% to be cost-saving [63]. In another study in South Africa, it has been shown that coverage of 40% of the population, which would prevent more than 73,000 deaths.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies on the monetary value of COVID-19 vaccines have been published so far (e.g., Hagens et al, 2021 ; Kohli, Maschio, Becker, & Weinstein, 2021 ; Marco-Franco, Pita-Barros, González-de-Julián, Sabat, & Vivas-Consuelo, 2021 ; Padula et al, 2021 ; Sandmann et al, 2021 ). Studies seem to concur that the clinical and economic value of COVID-19 vaccines is positive.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, differences exists in terms of healthcare systems, perspectives, methods, comparators, and prevailing coronavirus variants. Both a Turkish ( Hagens et al, 2021 ) and a U.K. study ( Sandmann et al, 2021 ) used a dynamic transmission model and – similar to this study – a societal perspective. While the Turkish study used no intervention as a comparator, the U.K. study considered a lockdown strategy.…”
Section: Discussionmentioning
confidence: 99%